2011
DOI: 10.1259/bjr/26062221
|View full text |Cite
|
Sign up to set email alerts
|

The use of central venous catheters for intravenous contrast injection for CT examinations

Abstract: ABSTRACT. The use of intravenous (iv) contrast media in CT examinations is often of great value in improving diagnostic accuracy. The preferable route of administration is via a peripheral iv cannula, with powered injectors allowing reliable delivery of rapid flow rates. However, many patients with a pre-existing central venous access device may have difficult peripheral access and there is a temptation to use the central device for delivery of contrast media. This review summarises the available evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 17 publications
0
21
0
3
Order By: Relevance
“…The sternal perforation led to the intramediastinal infusion. The clinical course of this case of mediastinal extravasation was uncomplicated, as is typical [10], likely due to the low volume if infused blood (approximately 150 ml). However, serious complications, including mediastinitis, hydrothorax, cardiac contusion, arterial perforation/dissection, or pneumothorax, have been described secondary to similar sternal intraosseous trocar perforations [3].…”
mentioning
confidence: 62%
“…The sternal perforation led to the intramediastinal infusion. The clinical course of this case of mediastinal extravasation was uncomplicated, as is typical [10], likely due to the low volume if infused blood (approximately 150 ml). However, serious complications, including mediastinitis, hydrothorax, cardiac contusion, arterial perforation/dissection, or pneumothorax, have been described secondary to similar sternal intraosseous trocar perforations [3].…”
mentioning
confidence: 62%
“…[10] In other cases, catheter fracture was not attributed to any cause other than mere weakening with prolonged use, without any external signs of damage, leading to catheter fatigue and therefore a shorter lifespan. [11] In this case, and although a power injector was not used, the catheter rupture was concluded to be a cause of high syringe pressure with the use of the standard 5 cc syringe for flushing when a 10 cc is currently recommended by the manufacturer. It is noteworthy to mention that almost all previous cases were reported in the adult oncology population in the setting of contrast or chemotherapeutic agent administration, and upon an extensive literature research, no cases were found in the pediatric population in association with a calcium infusion.…”
Section: Discussionmentioning
confidence: 88%
“…If a standard central venous catheter is the only available route for contrast injection, one may consider using the catheter according to the protocol proposed by Plumb and Murphy. 9 The clinician handling the line should receive training in execution of the protocol in order to minimise the risk of medical errors and poor patient outcomes. Furthermore, a radiologist with clearer knowledge of implanted ports should assist the clinician during management of the patient.…”
Section: Discussionmentioning
confidence: 99%